Determination Of Factors That Influence The Bid-Ask Spread In Companies Listed In The LQ45 Index For The 2018-2021 Period - Negara, Andi Kusuma; Humairoh, Humairoh; Khasanah, Iis Naning Nur (Journal of Accounting and Finance Management, 2024)
This research aims to determine the influence of company size, stock trading volume, stock return volatility, and dividend yield on the bid-ask spread in case studies of companies listed on the LQ45 Index during the 2018-2021 period on the Indonesia Stock Exchange. The population used in this research was 45 companies listed in the LQ45 Index. The technique used was a purposive sampling method to obtain 17 companies as sample results. Data were analyzed using panel data regression assisted by Eviews 10 software. This research provides results that partially company size has a significant influence on the bid-ask spread, but stock trading volume, stock return volatility, and dividend yield do not influence the bid-ask spread. If simultaneously company size, stock trading volume, stock return volatility, and dividend yield influence the bid-ask spread. Based on the determination results, the contribution given was 91.98%.